Spoken metaphor comprehension: Evaluation using the metaphor interference effect. Issue 3 (3rd April 2019) - Chouinard, Brea; Volden, Joanne; Hollinger, John; Cummine, Jacqueline
ABSTRACT: The metaphor interference effect (MIE) is a response time phenomenon wherein judging whether metaphorical sentences are literally true or false takes significantly longer than judging control sentences, indicating simultaneous generation of literal and nonliteral meanings during the integration stage. For written metaphor comprehension, word interactions during early processing, the contribution of working memory and IQ, and processing in clinical populations have been evaluated using written MIE tasks. Despite metaphor prevalence in everyday conversation, however, research aimed at understanding the MIE with spoken stimuli is absent. Our study determined whether the MIE would be elicited for spoken stimuli and compared the spoken and written conditions. In line with our primary objective, we provided evidence, for the first time, of the MIE in the spoken modality. We also found differences between the size of the spoken and written MIE, and for scrambled metaphor sentences. Scrambled metaphor differences may indicate processing differences for spoken versus written meaningless sentences, but this requires further investigation. Results are discussed in the context of metaphor processing.